2007
DOI: 10.1371/journal.pcbi.0030173
|View full text |Cite
|
Sign up to set email alerts
|

Structural Reorganisation and Potential Toxicity of Oligomeric Species Formed during the Assembly of Amyloid Fibrils

Abstract: Increasing evidence indicates that oligomeric protein assemblies may represent the molecular species responsible for cytotoxicity in a range of neurological disorders including Alzheimer and Parkinson diseases. We use all-atom computer simulations to reveal that the process of oligomerization can be divided into two steps. The first is characterised by a hydrophobic coalescence resulting in the formation of molten oligomers in which hydrophobic residues are sequestered away from the solvent. In the second step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
242
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(265 citation statements)
references
References 64 publications
22
242
1
Order By: Relevance
“…This notion is supported by a previous study in which only amorphous aggregates comprising Ͼ20 molecules of a tandem repeat construct of PI3-SH3 (equal to Ͼ40 individual domains), were found to be efficient in promoting ordered fibril formation (20). Furthermore, a recent molecular simulation study has shown that for a small fragment from the ␤-amyloid peptide (A␤ 16 -22 ), the barrier for the conformational conversion of disordered oligomers into ␤-sheet-rich structures is lower for larger species (29,30). Taken together, these findings indicate that although a broad ensemble of oligomer sizes may populate the pathway for amyloid fibril formation, oligomers within a specific range of sizes are required for efficient conversion into more ordered species.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…This notion is supported by a previous study in which only amorphous aggregates comprising Ͼ20 molecules of a tandem repeat construct of PI3-SH3 (equal to Ͼ40 individual domains), were found to be efficient in promoting ordered fibril formation (20). Furthermore, a recent molecular simulation study has shown that for a small fragment from the ␤-amyloid peptide (A␤ 16 -22 ), the barrier for the conformational conversion of disordered oligomers into ␤-sheet-rich structures is lower for larger species (29,30). Taken together, these findings indicate that although a broad ensemble of oligomer sizes may populate the pathway for amyloid fibril formation, oligomers within a specific range of sizes are required for efficient conversion into more ordered species.…”
Section: Resultsmentioning
confidence: 88%
“…4B for a sample incubated under aggregation conditions for 72 h. A plausible cause of this enhancement in stability is an internal conformational reorganization of the oligomeric species populated during the reaction that leads to fibril formation. Interestingly, such a process has been predicted in computer simulations of the early stages of amyloid formation and attributed to the nucleation of the cross-␤ structure within species whose coalescence is initially driven by the rapid formation of less stable hydrophobic interactions (29).…”
Section: Resultsmentioning
confidence: 97%
“…Several mechanisms have been proposed to explain amyloid fibril formation (24); among them, the nucleated conformational conversion (NCC) mechanism (25) is supported by a range of experimental and theoretical observations (26)(27)(28). In the NCC mechanism, a group of monomers initially present in solution coalesce to form amorphous oligomers.…”
Section: Discussionmentioning
confidence: 99%
“…3C), further reinforces the conclusion that a conformational change has occurred before their formation. This antibody is likely to recognize conformational characteristics of the intermediate species, perhaps because of the exposure of hydrophobic side chains (28,29) or the adoption of a different conformational form (30). The most protected residues in the O agg species are also the most protected ones in the F agg species, implying that these intermediates are likely to be species that progress to fibril formation.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, critical role of the oligomeric species isolated in the middle of fibrillation process should be acknowledged to evaluate the mechanism of amyloid fibril formation by acting as the seeds or the growing unit for the fibrillar assembly, in addition to their suggested pathological activity of causing cytotoxicity (104,105).…”
mentioning
confidence: 99%